Progress on Preparation of pH/Temperature-Sensitive Intelligent Hydrogels and Applications in Target Transport and Controlled Release of Drugs - Lixian Li; Yongpeng He; Xiaodong Zheng; Lin Yi; Weiqi Nian (International Journal of Polymer Science)
Hydrogels with three-dimensional network structure, hydrophilic, and insoluble in water which are ideal carrier materials for intelligent drug delivery systems. Intelligent hydrogel has become a research frontier and hotspot because of its intelligence, high efficiency, safety, and convenience in drug controlled and prolonged release. It has a broad application prospect in the medicine and biomedicine fields and can lead the medicine fields into a new era of “precise treatment.” Based on the latest research progress, the main preparation methods of hydrogel and the development of the drug delivery system are briefly introduced. The most promising three intelligent hydrogels in the human physiological environment, namely, pH responsiveness, temperature responsiveness, and pH/temperature dual responsiveness, are emphatically reviewed. Their release mechanisms, targeting transport, and controlled-prolonged release of drug are also discussed. In addition, some suggestions for the main problems and future development were given.